ANALISIS PENGARUH REFLECTOR BOLIC PADA ANTENA MIKROSTRIP DALAM MENINGKATKAN PENGUATAN SINYAL WIFI - Febri Handoko . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2018)
Wireless computer network that is popular right now are the types of internet networks are Local Area Networks (LAN) and Wireless Local Area Networks (WLAN). The application of WLAN cannot be separated from the main equipment, the antenna. This  final  project to examine the design of the microstrip antennas and observe the influence of bolic reflectors in increasing Wi-Fi signal gain. The application used is acrylic wi-Fi home software this research is acrylic wi-fi home which is used to measure signal quality, rainforcement gain and the number of access points. Based on the telecommunication laboratory test, the average results of the microstrip antenna with the reflector at a distance of 5 m, 10 m, 15 m and 20 m is -58 dBm, -67 dBm, -68 dBm and -68 dBm while the avarage without the reflector  is -65 dBm, -74 dBm, -75 dBm, and -75 dBm. The total antenna gain on the four distances is increased by 8 dBm.Keywords: Effect of Bolic Reflector, Reflector Bolic, Microstrip Antenna, WLAN